ANALISIS FAKTOR-FAKTOR PENDING KLAIM BPJS KESEHATAN RAWAT INAP PERIODE TRIWULAN IV TAHUN 2024 DI RUMAH SAKIT UMUM DAERAH TANGERANG SELATAN - Christin, Rumondang; Lestari, Santi; Pratiwi, Rita Dwi; Muchtar, Riska Indria (EDU RMIK Jurnal Edukasi Rekam Medis Ilmu Kesehatan, 2025)
Claim pending for BPJS Kesehatan at the Regional General Hospital (RSUD) of South Tangerang is a significant issue, affecting the hospital's administrative and financial efficiency. Based on a preliminary study, the main causes of pending claims include incomplete documents such as service procedure reports, supporting examination results, and diagnosis revisions. This research aims to identify the factors influencing inpatient claim pendings for BPJS Kesehatan at RSUD South Tangerang. A quantitative approach with a retrospective design was used. Data were collected through document observation, questionnaires, and interviews with 14 casemix officers, along with an analysis of 224 pending claim files. The sampling technique applied was simple random sampling, and data were analyzed descriptively to identify the percentage of document incompleteness and the underlying causes of claim pending. The results showed that the implementation of the Standard Operating Procedure (SOP) for claim submission had reached 86%, although SOP socialization was still uneven. Human resources in the casemix unit were dominated by graduates of the Associate Degree in Medical Records (50%), while 7% of staff had only completed high school or equivalent. Incomplete documentation was identified as the main cause of claim pending, with incomplete diagnosis codes (53%), incomplete supporting documents (46%), and incomplete service evidence (13%).